Effects of Caffeine on Egg Quality and Performance of Laying Hens - Teixeira, Mailson da Silva; Triginelli, Marcela Viana; Costa, Thaís de Ataíde; Lara, Leonardo José Camargos; Soto-Blanco, Benito (Frontiers in Veterinary Science, 2020)
This study's objective was to determine the effects of caffeine intake at various levels, incorporated in the layers' food, on performance and egg quality of hens. A total of 576 hens, aged 56 weeks, were used. The layers were fed rations containing 0 (control), 150, 300, or 450 ppm of caffeine for twelve weeks. During the experimental period, performance parameters (weight, feed consumption, and livability) and egg production and quality (weight, Haugh unit, percentages of yolk, albumen and eggshell, yolk color, eggshell thickness, and resistance, and calcium and phosphorus eggshell contents) were evaluated. The highest concentration of caffeine in the diet (450 ppm) promoted a significant increase in the mortality of hens (1.45% per week) compared to controls (0.23%). There was a reduction in feed consumption by hens, decreased egg production, and reduced eggshell thickness and percentage, with the increase of caffeine. The egg yolk percentage was increased, and the eggshell percentage was reduced in the groups treated with 300 ppm and 450 ppm of caffeine. Furthermore, reduced eggshell thickness was found in all groups that received caffeine. However, it was found that 150 ppm of caffeine in the food did not cause significant changes in most egg production and quality parameters. In summary, caffeine consumption by laying hens increased mortality rate and promoted deleterious effects on chicken production and egg quality at concentrations of 300 and 450 ppm.